Kebisingan Terhadap Gangguan Auditori dan Non Auditori pada Karyawan PT PLN - Amalya, Eka Rizka; Fachrin, Suharni A; Gobel, Fatmah Afrianty; Hardi, Ikhram; Ahri, Reza Aril; Baharuddin, Alfina (Lontara Journal of Health Science and Technology, 2024)
Noise has several impacts on health. Besides the impact on hearing loss, high noise intensity can also cause loss of concentration, loss of balance and disorientation, fatigue, and communication disorders. This research design is analytic survey with cross sectional study approach. The location of this research is at PT PLN Persero Persero West Halmahera, North Maluku Province. The population was 123 people. The sample was 94 people with purposive sampling technique. The results obtained P value = 0.000 (P <0.05) means there is an influence of noise. The results of statistical chi-square test obtained P value = 0.003 (P <0.05) means that there is an effect of noise on physiological disorders. P value = 0.006 (P <0.05) means that there is an effect of noise on psychological disorders P-value 0.000 means that there is an effect of noise on work productivity Conclusion there is an effect of noise on communication disorders psychological disorders, work productivity disorders and physiological disorders in employees